2007
DOI: 10.1073/pnas.0610860104
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of mammary cancer inhibition by combination of antagonists of growth hormone-releasing hormone with docetaxel

Abstract: breast cancer ͉ cancer therapy ͉ chemotherapeutic agents ͉ growth hormone-releasing hormone receptors

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
28
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 50 publications
4
28
0
3
Order By: Relevance
“…In previous breast cancer studies independent of the receptor status an inhibition of proliferation was observed, for example, in T47D estrogen receptor positive breast cancer cells by a GHRH antagonist in vitro [29] and in MXT mouse mammary cancer in vivo [16]. In a recent study we could show that in human estrogen receptor negative MX-1 breast cancers GHRH antagonists lead to marked inhibition of tumor growth in a nude mice model [42]. It was also demonstrated in this model, that co-treatment with a GHRH antagonist potentiated the antitumor effect of docetaxel [42], suggesting that GHRH antagonists are suitable partners for conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In previous breast cancer studies independent of the receptor status an inhibition of proliferation was observed, for example, in T47D estrogen receptor positive breast cancer cells by a GHRH antagonist in vitro [29] and in MXT mouse mammary cancer in vivo [16]. In a recent study we could show that in human estrogen receptor negative MX-1 breast cancers GHRH antagonists lead to marked inhibition of tumor growth in a nude mice model [42]. It was also demonstrated in this model, that co-treatment with a GHRH antagonist potentiated the antitumor effect of docetaxel [42], suggesting that GHRH antagonists are suitable partners for conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 88%
“…In a recent study we could show that in human estrogen receptor negative MX-1 breast cancers GHRH antagonists lead to marked inhibition of tumor growth in a nude mice model [42]. It was also demonstrated in this model, that co-treatment with a GHRH antagonist potentiated the antitumor effect of docetaxel [42], suggesting that GHRH antagonists are suitable partners for conventional chemotherapy.…”
Section: Discussionmentioning
confidence: 91%
“…As a proof of concept hGHRH analogs, JI-34 and JI-36, were able to induce a rise in intracellular calcium. In the same line, the selective hGHRH-R antagonists, JV-1-42 and JMR-132 (23)(24)(25)(26), behave as antagonists of the ghrelin receptor GHS-R1a. Finally, and quite remarkably, GHRH activated the endocytosis of the ghrelin receptor.…”
Section: Discussionmentioning
confidence: 94%
“…Growth hormone-releasing hormone antagonists suppress the in vivo growth of various experimental cancers such as prostatic (Zarandi et al, 2006;Stangelberger et al, 2007), mammary (Buchholz et al, 2007), ovarian (Chatzistamou et al, 2001), renal cell carcinomas , small cell lung carcinomas (Hohla et al, 2006), pancreatic and colorectal carcinomas (Szepeshazi et al, 2000;Busto et al, 2002), endometrial (Engel et al, 2005), osteogenic sarcomas (Braczkowski et al, 2002) as well as malignant glioblastomas (Jaeger et al, 2005).…”
mentioning
confidence: 99%